2022
DOI: 10.3389/fnut.2022.977403
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient patterns and non-alcoholic fatty liver disease in Iranian Adul: A case-control study

Abstract: BackgroundsThe current literature boasts the importance of diet in preventing or managing liver complications. However, there is limited evidence on the association of nutrient patterns (NP) with these complications. In this case-control study, we aimed to examine the possible relationship between nutrient patterns and the risk of non-alcoholic fatty liver disease (NAFLD) amongst the adult Iranian population.MethodsThis case-control study is being conducted at the Metabolic Liver Disease Research Center at Isf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In fact, the major nutrients of DFP1, e.g., dietary fiber, potassium, folate, carotene, vitamin C, B6, and E, were mostly enriched in vegetables and fruits ( 35 , 36 ). The benefit of vegetarian diet is also supported by previous studies from diverse populations ( 14–16 ), indicating the generalizability of vegetarian food in the management of NAFLD patients.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In fact, the major nutrients of DFP1, e.g., dietary fiber, potassium, folate, carotene, vitamin C, B6, and E, were mostly enriched in vegetables and fruits ( 35 , 36 ). The benefit of vegetarian diet is also supported by previous studies from diverse populations ( 14–16 ), indicating the generalizability of vegetarian food in the management of NAFLD patients.…”
Section: Discussionsupporting
confidence: 68%
“…Studies on dietary patterns established according to typical dietary populations may be more beneficial to provide practicable clinical strategies on diet ( 13 ). The vast majority of current research studying the role of dietary patterns on NAFLD has been designed using food groups, while only a small number of studies were performed using nutrient intakes ( 14–16 ). Using nutrient intakes to identify dietary patterns enables the understanding of key biological processes and makes it easier to compare results between different populations ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that a nutrient pattern characterized by high intake of calcium, potassium, fats, cholesterol, vitamins B2, B12, A, D, K and C was positively linked to MetS [ 23 ]. Salehi-Sahlabadi et al found that adhering to a nutrient pattern rich in potassium, vitamin A, fructose, vitamin C and vitamin B6 was negatively associated with the likelihood of NAFLD [ 11 ]. A nutrient pattern high in potassium, vitamin A, vitamin B6, vitamin C and fructose was associated with a reduced risk of hyperinsulinemia, IR, and dyslipidemia among participants in Tehran, according to a prospective study [ 11 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no specific treatment for this condition other than lifestyle correction [ 25 ]. A recent study showed that a healthy diet, based on the consumption of fruits, vegetables, and nuts, as well as important sources of vitamin A, vitamin C, pyridoxine, and potassium, is inversely associated with the risk of MASLD [ 26 ].…”
Section: Introductionmentioning
confidence: 99%